UPAYA PENINGKATAN KEMAMPUAN SISWA DALAM MENJAWAB PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Jumaiti Sabri (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
The research was conducted as an effort to improve students' ability in learning the Indonesian language using Visual Media Audio as part of improving student learning. Improving students 'abilities must be supported by teachers who have good creativity and motivation to improve students' abilities in learning. Indonesian Language Learning is a daily language of students that need to be managed properly, especially related to the teaching method. The results showed that: First: the average Indonesian language learning outcomes of class III students increased by 10.35 points from Pratindakan (58.93) to Cycle I (69.28), an increase of 11.61 points from Cycle I to Cycle II (80.89), and increased by 21.96 points from Primary actions to the end of the action. Second, the percentage of completeness in learning Indonesian language students showed an increase from Pratindakan (21.43%), Suklus I (92.85%), to Cycle II (96.43%). Third, through audiovisual media methods can improve Indonesian language learning outcomes of third-grade students of SDN 018 Tenggarong in the academic year 2018/2019. Fourth, learning methods using audiovisual media can activate students in the process of learning Indonesian in answering questions. Keywords: Learning, Indonesian, Audio Visual.